Modell för beskrivning av kollokationer i ett medicinskt lexikon (MedLex) - Sköldberg, Emma; Toporowska Grono, Maria (Nordiske Studier i Leksikografi, 2007)
The paper presents a pilot study of the treatment of collocations in an electronic medical lexicon, MedLex, currently under construction at the University of Gothenburg, Department of Swedish. The lexicon is descriptive and intended to support both reception and production. The study focuses on noun collocations, especially those which describe diseases and medical conditions. We present an analysis model based on a combination of semasiological and onomasiological premises. The model results in a classification into lexically conditioned collocations and type-related collocations. We also discuss how medically related collocations may be described in the MedLex lexicon.